Early investigation of the impact of mobile learning ethics student-generated activities for STEM subjects in a local Malaysian university context - Shamsul Arrieya, Ariffin; Glahn, Christian; Muh, Anshar; Faiz, Daud; Tee, Tze Kiong; Nurul Hazlina, Noordin; Amirrudin, Kamsin (International Association of Online Engineering, 2020)
Mobile learning is fairly new in the local context, particularly for STEM subjects in Malaysia universities. However, this raises the issue of the ethics of mobile technology. With the advancement of mobile technologies few studies have been conducted for mobile ethics in student-generated activities. The aim of this research is to investigate the impact of mobile learning student-generated activities ethics in Malaysia. The methodology used in this research is largely qualitative with students from a local university in Malaysia. This novel study developed early themes that sign post factors for mobile ethics in student-generated activities in a Malaysian university context for STEM subjects.